Clinical Utility of the Japan–Chronic Total Occlusion Score in Coronary Chronic Total Occlusion Interventions. (July 2015) - Christopoulos, Georgios; Wyman, R. Michael; Alaswad, Khaldoon; Karmpaliotis, Dimitri; Lombardi, William; Grantham, J. Aaron; Yeh, Robert W.; Jaffer, Farouc A.; Cipher, Daisha J.; Rangan, Bavana V.; Christakopoulos, Georgios E.; Kypreos, Megan A.; et al.
<x xml:space="preserve">Abstract</x> Background— The performance of the Japan–chronic total occlusion (J-CTO) score in predicting success and efficiency of CTO percutaneous coronary intervention has received limited study. Methods and Results— We examined the records of 650 consecutive patients who underwent CTO percutaneous coronary intervention between 2011 and 2014 at 6 experienced centers in the United States. Six hundred and fifty-seven lesions were classified as easy (J-CTO=0), intermediate (J-CTO=1), difficult (J-CTO=2), and very difficult (J-CTO≥3). The impact of the J-CTO score on technical success and procedure time was evaluated with univariable logistic and linear regression, respectively. The performance of the logistic regression model was assessed with the Hosmer–Lemeshow statistic and receiver operator characteristic curves. Antegrade wiring techniques were used more frequently in easy lesions (97%) than very difficult lesions (58%), whereas the retrograde approach became more frequent with increased lesion difficulty (41% for very difficult lesions versus 13% for easy lesions). The logistic regression model for technical success demonstrated satisfactory calibration and discrimination (P for Hosmer–Lemeshow =0.743 and area under curve =0.705). The J-CTO score was associated with a 2-fold increase in the odds of technical failure (odds ratio 2.04, 95% confidence interval 1.52–2.80, P<0.001). Procedure time increased by ≈20 minutes for every 1-point increase of the J-CTO score (regression coefficient 22.33, 95% confidence interval 17.45–27.22, P<0.001). Conclusions— J-CTO score was strongly associated with final success and efficiency in this study, supporting its expanded use in CTO interventions. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT02061436.